Economic Development and Female Labour Force Participation: The Case of European Union Countries - Altuzarra, Amaia; Gálvez-Gálvez, Catalina; González-Flores, Ana (Sustainability, 2019)
In this paper, we studied the relationship between female labour force participation and economic development in the 28 countries of the European Union during the period 1990–2016. The analysis was carried out from two different viewpoints: first, we studied all the countries of the EU-28, and second, the evidence was disaggregated into two groups of countries: old (EU-15) and new (EU-13) member estates. The data used came from the World Bank open data repository and Eurostat. The methodology used consisted of the estimation of static (Ordinary Least Squares (OLS) and Fixed Effects (FE)) and dynamic (generalized moments model—GMM) models. Results for all European countries (EU-28) were consistent with the hypothesis which suggests the existence of a U-shaped relationship between female labour force participation and economic development. When the sample was broken down into groups, we found evidence that confirms the feminization hypothesis for the new countries of the EU, but not for the old ones.